Implementasi Perlindungan Hukum Bagi Advokat dalam Pelaksanaan Hak Pembelaan pada Perkara Pidana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
In this study, advocates are guaranteed legal protection to implement the right to defence in criminal cases. to learn how criminal advocates are protected if they enforce the law. The privilege of immunity shields advocates from civil or criminal litigation for good faith work inside and outside the court. This study uses normative juridical research, which examines current laws and regulations. Analysis of relevant legislation is needed for this research. According to the study, Article 16 of Law Number 18 of 2003 concerning Advocates does not adequately describe advocates' immunity rights. Lack of clear explanations of protection types, rights constraints, and good faith between advocates and other parties may lead to power abuses. More extensive norms that are in keeping with other articles of the law are needed to apply advocates' immunity rights proportionately, guaranteeing freedom in performing their profession while maintaining society's and justice's legal interests.